The Effect of Selective D- or Nα-Methyl Arginine Substitution on the Activity of the Proline-Rich Antimicrobial Peptide, Chex1-Arg20 - Li, Wenyi; Sun, Zhe; O'Brien-Simpson, Neil M.; Otvos, Laszlo; Reynolds, Eric C.; Hossain, Mohammed A.; Separovic, Frances; Wade, John D. (Frontiers in Chemistry, 2017)
In vivo pharmacokinetics studies have shown that the proline-rich antimicrobial peptide, A3-APO, which is a discontinuous dimer of the peptide, Chex1-Arg20, undergoes degradation to small fragments at positions Pro6-Arg7 and Val19-Arg20. With the aim of minimizing or abolishing this degradation, a series of Chex1-Arg20 analogues were prepared via Fmoc/tBu solid phase peptide synthesis with D-arginine or, in some cases, peptide backbone N-methylated arginine, substitution at these sites. All the peptides were tested for antibacterial activity against the Gram-negative bacterium Klebsiella pneumoniae. The resulting activity of position-7 substitution of Chex1-Arg20 analogues showed that arginine-7 is a crucial residue for maintaining activity against K. pneumoniae. However, arginine-20 substitution had a much less deleterious effect on the antibacterial activity of the peptide. Moreover, none of these peptides displayed any cytotoxicity to HEK and H-4-II-E mammalian cells. These results will aid the development of more effective and stable PrAMPs via judicious amino acid substitutions.